Visual and Anatomical Outcome Of Ozurdex Implant In Non-Infectious Intermediate Or Posterior Uveitis In Treatment Naive Patients - Navneet Mehrotra; Manish Nagpal; Hardik Jain; Rakesh Juneja (Delhi Journal of Ophthalmology)
Aim:- To determine the visual and anatomical outcome of Ozurdex implant in non-infectious intermediate or posterior uveitis in treatment naïve patients. Design:- Retrospective study. Materials and Methods:- 25 eyes receiving Ozurdex implant (0.7mg dexamethasone) for treatment of naïve non-infectious intermediate or posterior uveitis with cystoid macular edema (CME) having a minimum 6 month follow up. Best corrected visual acuity (BCVA) and central foveal thickness (CFT) was measured at baseline, 1, 3 & 6 months. Results:- Mean baseline logMAR BCVA improved significantly from 0.477 to 0.181 (p<0.05) at 3 months and to 0.193 (p<0.05) at 6 months. The mean CFT reduced from its baseline value of 481.3µto 250.41µ (p<0.05) at 3 months and to 274.8µ(p<0.05) at 6 months. Conclusion:- Significant improvement in BCVA and CFT from baseline to 3 and 6 months has proven Ozurdex implant to be a promising treatment option in cases of treatment naïve non-infectious posterior uveitis.